MOTIVATION OF TRAVELERS FOR PARTICIPATION IN WINE TOURISM IN SERBIA - Sekulić, Dejan; Mandarić, Marija; Milovanović, Vesna (Economics of Agriculture, 2016)
The aim of this papper is to investigate the motives of tourists for participating in wine tourism in Serbia. The research was conducted using the survey method. From the total number of sent questionnaires, there was received 160 fully completed ones. Results of the research show that the most important motives for the inclusion of tourists to the wine tourism are: wine tasting, trying different sorts of wines, visiting wineries, getting information about wine and its production and organization of the trip. Wine tourists showed a high degree of readiness to visit wineries that produce their favorite wine. Secondary motives of wine tourists are: participating in the production of wine, visiting shops that sell local products and meeting people with similar interests. Motivation of tourists is the driving force that affects their intention to visit a wine destination and take part in wine tourism. On the other hand, barriers such as free time, distance of wine regions and fnancial expenditure do not signifcantly affect the motivation and future behavior of wine tourists.